Konsep Pendidikan Untuk Perempuan Perspektif Nyai Hj. Masriyah Amva - Atiq Nur Dianti (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2020)
One figure of a well-known female cleric in Cirebon is Nyai Hj. Masriyah Amva. He is a female ulama figure who is different from the others, Nyai Hj. Masriyah Amva became the caretaker of Kebon Jambu Al-Islamy Islamic Boarding School in Babakan Village, Ciwaringin Cirebon, where she became the leader of more than 1,000 male and female santri. The author presents this paper in the form of a qualitative approach, with qualitative descriptive methods, collection techniques using interview and observation methods, which are then analyzed by interactive analysis techniques namely data reduction, data presentation and drawing conclusions. This study aims to illustrate the Concept of Education for Perpective Women Nyai Hj. Masriyah Amva at Kebon Jambu Al-Islamy Islamic Boarding School. According to him, education for women consists of material elements, immaterial elements and character elements. The material element is education that equips students with various sciences according to their respective levels, while the immaterial element is that women are able to present and involve the Creator in all their life processes, according to Nyai Hj. Masriyah Amva, that is, women must be educated in such a way as to form a woman who is persistent, independent, has a personality, is pious and tough with hard prayers, hard efforts and always has positive thoughts.Salah satu sosok ulama perempuan yang sangat dikenal di Cirebon adalah Nyai Hj. Masriyah Amva. Beliau adalah sosok ulama perempuan yang berbeda dengan lainnya, Nyai Hj. Masriyah Amva menjadi pengasuh Pondok Pesantren Kebon Jambu Al-Islamy di Desa Babakan, Ciwaringin Cirebon, beliau menjadi pemimpin lebih dari 1.000 santri laki-laki dan perempuan. Penulis menyajikan tulisan ini dalam bentuk pendekatan kualitatif, dengan metode deskriptif kualitatif, teknik pengumpulan menggunakan metode wawancara dan observasi, yang kemudian dianalisis dengan teknik analisis interaktif yaitu reduksi data, penyajian data dan penarikan kesimpulan. Penelitian ini bertujuan untuk menggambarkan Konsep Pendidikan untuk Perempuan Perpektif Nyai Hj. Masriyah Amva di Pondok Pesantren Kebon Jambu Al-Islamy. Menurutya pendidikan untuk perempuan adanya unsur material, unsur imaterial dan unsur karakter. Unsur material adalah pendidikan yang membekali santrinya dengan berbagai ilmu pengetahuan sesuai jenjangnya masing-masing, sedangkan unsur Imaterial adalah para perempuan mampu menghadirkan dan melibatkan Sang Pencipta dalam semua proses kehidupannya, unsur karakter menurut Nyai Hj. Masriyah Amva yaitu perempuan harus dididik sedemikian rupa hingga terbentuklah sosok perempuan yang gigih, mandiri, berkepribadian, bertaqwa dan tangguh dengan do`a keras, usaha keras dan selalu berfikiran positif.